2010
DOI: 10.3758/s13415-010-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dichotical fusion on the redundant signals effect, localization performance, and the mismatch negativity

Abstract: In two experiments, each including a simple reaction time (RT) task, a localization task, and a passive oddball paradigm, the physical similarity between two dichotically presented auditory stimuli was manipulated.In both experiments, a redundant signals effect (RSE), high localization performance, and a reliable mismatch negativity (MMN) was observed for largely differing stimuli, suggesting that these are coded separately in auditory memory. In contrast, no RSE and a localization rate close to chance level (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…The only other research of which we are aware, that has applied concepts from the redundant signals RT approach to binaural perception is a seminal study by Schröter et al (2007) and extended in Schröter et al (2009) and Fiedler et al (2011). Schröter et al (2007) employed the Miller (1982) inequality to assess binaural vs. monaural performance but did not assess performance in terms of the standard parallel model or the Grice bound for extreme limited capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The only other research of which we are aware, that has applied concepts from the redundant signals RT approach to binaural perception is a seminal study by Schröter et al (2007) and extended in Schröter et al (2009) and Fiedler et al (2011). Schröter et al (2007) employed the Miller (1982) inequality to assess binaural vs. monaural performance but did not assess performance in terms of the standard parallel model or the Grice bound for extreme limited capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, ‘actions’ also encompass inhibition of motor responses (Hommel et al., ). In addition, also bimodal stimuli affect response inhibition (Cavina‐Pratesi, Bricolo, Prior, & Marzi, ; Chmielewski, Mückschel, Dippel, & Beste, ; Chmielewski, Wolff, Mückschel, Roessner, & Beste, ; Fiedler, Schröter, Seibold, & Ulrich, ; Gondan, Götze, & Greenlee, ). Such ‘inhibitory control’ is of particular interest since GTS has long been considered a disorder of inhibitory control.…”
Section: Introductionmentioning
confidence: 99%
“…Integration at higher centers in the auditory system is important for the perception of one fused auditory image. Fiedler and colleagues found that dichotically presented pure tones were both perceived as fused and integrated cortically, as indicated by the absence of a mismatch negativity waveform [ 46 ]. Despite normal cortical development promoted by CI use [ 5 , 6 , 94 ], deviations from normal remain [ 7 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activity in the cortex is also believed to reflect integration [ 46 ]. When cortical activity was recorded with electroencephalography during a passive oddball task, the mismatch negativity waveform was only non-significant for stimuli presented dichotically and with small interaural frequency differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation